RANCANG BANGUN WATER LEVEL CONTROL BERBASIS SONOFF SMART SWITCH - Yudhi Agussationo; Sepdian; Andi Rajanudin (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2022)
The prototype of an automatic water tank filling system based on a sonoff smart switch that works based on the volume of water level in a tank based on a sonoff smart switch has been successfully created. This study aims to determine the working principle of the sonoff switch and automatic water tank filling system. The water sensor used in this study is a float switch type that works based on changes in the value of the high volume of the tank water. For automatic filling of the water tank, a sonoff smart switch and also a float switch have been used as a switch to drain and disconnect the electric current to the pump. The design results show that this automatic water tank filling system can work well, where if the water tank level is below 20% then the water pump will turn "ON" and if the water level in the tank is above 90% then the water pump will turn "OFF".